ANALISIS STRATEGI PEMASARAN DENGAN MENGGUNAKAN METODE SWOT TERHADAP KEPUASAN KONSUMEN (STUDI KASUSUD. FROTUNA BROWNIES KUKUS GRESIK) - Khadijah, S.E., M.M., Susan Novitasari (Fakultas Ekonomi Universitas Gresik, 2020)
The purpose of this study is to identify the factors that most influence consumer satisfaction at UD. Fortuna Brownies Kukus Gresik is based on analysis from the marketing mix (Product, Price, Place and Promotion) to determine alternative marketing strategies for gresik steamed brownies based on the SWOT analysis. The results of this study indicate that there is a relationship simultaneously Marketing mix has an effect on consumer satisfaction. Price variable as the dominant variable influencing consumer satisfaction. The results of the SWOT IFE (internal factor evaluation) and EFE (eksternal factor evaluation) matrix analysis show UD. Fortuna Brownies Gresik steamer is in quadrant 1 which means that the strategy used is the strategy of Strengths Opportunies (SO) or Growth strategy which shows that UD. Fortuna Brownies steamed Gresik belongs to a growing business and has a strong position and opportunity.Ãƒâ€šÃ‚Â